Pengaruh Metode Pembelajaran Small Group Work Terhadap Hasil Belajar Ilmu Pengetahuan Sosial Siswa Madrasah Tsanawiyah Negeri 8 Kampar - Ayu Widya Astuti; Devi Arisanti; Syakila Syakila; Alimuddin Alimuddin; Darni Darni (GLOBAL SCIENTS PUBLISHER, 2025)
This research aimed at finding out the significant effect of Small Group Work learning method toward student social science learning achievement at State Islamic Junior High School 8 Kampar. This research was instigated with the low student learning achievement, including the lack of student knowledge of Social Science learning material and the lack of student ability to communicate in group discussions. Quantitative method was used in this research with quasi-experimental approach. All the seventh-grade students were the population of this research, and they were 132 students. While the samples consisted of 66 students, they were the seventh-grade students of classes 1 and 2, and they were selected with purposive sampling technique. Test, observation, and documentation were used to collect data. Based on the research findings and data analyses, there was a significant effect of Small Group Work learning method toward student social science learning achievement at State Islamic Junior High School 8 Kampar. It could be identified from the experimental posttest mean score 78.33 and the control posttest mean score 69.85. Based on the independent sample t-test results, tobserved was higher than ttable (6.847>1.669), so it could be concluded that Ha was accepted, and H0 was rejected. The effect size test results showed that the score was 0.69, so there was a moderate effect of Small Group Work learning method toward student social science learning achievement at State Islamic Junior High School 8 Kampar.